Influence of Cyberspace on Changes in Contemporary Education - Slavomír Gálik, (Communication Today, 2025)
Cyberspace of digital media changes contemporary education in two ways: by a new approach to understanding information and a new way of organising this information. In the first case, it is objectification of information that favours the idea of a reduced type of education, based on certain extent of knowledge that is applicable in practice. In our approach, we emphasise the fact that information cannot be taken merely as an object, but also as a contextual and unlimited semantic unit which, through a new organisational level, becomes knowledge. Besides information and knowledge, higher level of cognition requires tacit human features – creativity and wisdom, as well as moral character of man. The second case brings a net-like structure of information, characterised by loop processing, prompt (almost immediate) linking of information that is predominantly image-based. This type of communication and organisation of information is useful because it gives us a fast way of searching for information and – perhaps – more creativity as well. However, it quite possibly implies a risk of weakening some of the cognitive abilities of man (such as logical and abstract thinking), vital not only in the scientific activities, but also in the everyday life. Under influence of communication within cyberspace, contemporary education is beginning to dramatically turn away from discursive (logical, abstract) thinking to associative (especially image-based) thinking. These new trends in education are reflected on really negatively by many authors, for example by M. Bauerlein, N. Carr, K. P. Liessmann or M. Spitzer, as they demand certain ‘counteraction’ which should be based on literacy, critical thinking, information hygiene and which should also become an important component of modern media education.